The Effectiveness of the Dialogical Method in Religious Education - Stanisław Radoń (Nicolaus Copernicus University in Toruń, 2011)
This article validates the role of dialogical methods in religious education. Pedagogical and psychological research suggests that a dialogue between teachers and students is essential to facilitating the development of critical and creative consciousness. An experiment was conducted to predict the effectiveness of the dialogical method in religious education. 250 students took part in a survey compiled for the purpose of the test. Descriptive statistics was applied to carry out the survey analysis. The results confirmed that a student-centered dialog is an effective method in religious education.